Steps of using transformation matrixto analyze kinematics of specific planar mechanism - Phan , Thanh Nhan (Journal of Technical Education Science, 2021)
Currently, when analyzing kinematics of machines and mechanism, most students in universities often use a familiar method (called graphical kinematic analysis) that sketches position, velocity, and diagrams. Graphical kinematic analysis is considered as a simple, intuitive approach but less accurate because values of kinematic quantities are measured from graphical vector diagrams. Moreover, when the input parameters such as length of links, angular velocity of the input link… are changed the calculation process must be repeated from the beginning that consumes much time. Kinematic analysis is a more advanced method thanks to using precise mathematical operations and easy to automate. There are many kinematic analytical methods introduced in some documents in universities but most of them are difficult to use because of complicated application. Using the transformation matrix to analyze kinematics of planar mechanisms is considered as an appropriate, easy-to-use method that can overcome drawbacks of the graphical method. In order to assist students step by step to apply a new method of calculating planar mechanism kinematics, this article will detail the steps of applying the transformation matrix to analyze kinematics of one specific planar mechanism. Finally, the article will show the graphs of location, velocity, and acceleration obtained from a program written in MatLab programming language.